1998
DOI: 10.1063/1.477286
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric properties of pyridinium periodate

Abstract: Articles you may be interested in[N(CH3)3H]2ZnCl4: Ferroelectric properties and characterization of phase transitions by Raman spectroscopy J. Appl. Phys. 116, 214104 (2014); 10.1063/1.4903303 Ferroelectric domain wall relaxation in Ba 0.25 Sr 0.75 Ti O 3 films displaying Curie-Weiss behavior

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 16 publications
0
41
0
Order By: Relevance
“…Depending on their symmetry and the size of anions, these compounds exhibit a large variety of interesting phenomena: phase transitions, ferroelectricity, dynamic orientational disorder of pyridinium cations, etc., [1][2][3][4]. The ferroelectric state was observed in pyridinium tetrafluoroborate PyHBF 4 (C 5 H 5 NHBF 4 ) [1], pyridinium perchlorate PyHClO 4 [2], pyridinium perrhenate PyHReO 4 [3], and pyridinium periodate PyHIO 4 [4]. Interest in studying the latter two compounds listed above is connected with the fact that their Curie temperatures are close to room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on their symmetry and the size of anions, these compounds exhibit a large variety of interesting phenomena: phase transitions, ferroelectricity, dynamic orientational disorder of pyridinium cations, etc., [1][2][3][4]. The ferroelectric state was observed in pyridinium tetrafluoroborate PyHBF 4 (C 5 H 5 NHBF 4 ) [1], pyridinium perchlorate PyHClO 4 [2], pyridinium perrhenate PyHReO 4 [3], and pyridinium periodate PyHIO 4 [4]. Interest in studying the latter two compounds listed above is connected with the fact that their Curie temperatures are close to room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of ferroelectricity was discovered in pyridinium tetrafluoroborate PyHBF 4 (C 5 H 5 NHBF 4 ) [1], pyridinium perchlorate PyHClO 4 [2], pyridinium perrhenate PyHReO 4 [3] and pyridinium periodide PyHIO 4 [4]. Two latter compounds are of special interest because their Curie temperatures are above room temperature.…”
Section: Introductionmentioning
confidence: 98%
“…Pyridinium salts exhibit a rich variety of interesting phenomena, such as ferroelectricity, polymorphic phase transformations and orientational dynamical disorder [1][2][3][4]. The existence of ferroelectricity was discovered in pyridinium tetrafluoroborate PyHBF 4 (C 5 H 5 NHBF 4 ) [1], pyridinium perchlorate PyHClO 4 [2], pyridinium perrhenate PyHReO 4 [3] and pyridinium periodide PyHIO 4 [4].…”
Section: Introductionmentioning
confidence: 98%
“…[13][14][15][16] In PyHBF 4 and PyHClO 4 , in their high-temperature phases (I), the reorientations take place between the equivalent minima of potential energy, while in the intermediate phases (II) and the low-temperature phases (III), the reorientations take place between the minima of different values. The 1 H NMR measurements performed as a function of temperature and pressure for PyHIO 4 have shown that in the ferroelectric phases (the intermediate (II) and low-temperature (III)), the cation reorientations take place between the potential energy minima of different values and have suggested that in the paraelectric phase (the high-temperature phase (I)), the pyridinium cation undergoes reorientations through equivalent potential barriers.…”
Section: Introductionmentioning
confidence: 99%